Ocular vestibular-evoked myogenic potential (oVEMP) to test utricular function: neural and oculomotor evidence - CURTHOYS, I.S. (Pacini Editore SpA, 2012)
A new test for utricular function has recently been introduced and validated, namely the ocular vestibular-evoked myogenic potential (oVEMP), which refers to the myogenic potentials recorded by surface EMG electrodes beneath both eyes in response to bone conducted vibration (BCV) of the head or air conducted sound (ACS). The oVEMP test differs from another vestibular-evoked myogenic potential recorded by surface EMG electrodes over the sternocleidomastoid muscles in that the cervical vestibular-evoked myogenic potential (cVEMP) due to saccular activation is measured. oVEMP is a reliable clinical test that relies on extensive physiological evidence from studies on guinea pigs, and in particular on recording the vestibular primary afferent responses to BCV, demonstrating that the same BCV causes similar eye movements in both guinea pigs and humans. This review briefly integrates the most recent physiological and behavioural evidence that substantiates the clinical use of oVEMP.